2013
DOI: 10.1017/jns.2013.12
|View full text |Cite
|
Sign up to set email alerts
|

Mood improvement in young adult males following supplementation with gold kiwifruit, a high-vitamin C food

Abstract: Enhanced intakes of fruit and vegetables have been associated with improved psychological well-being. We investigated the potential mood-enhancing effects of kiwifruit, a fruit rich in vitamin C and a number of other important micronutrients. Young adult males (n 35) were supplemented with either half or two kiwifruit/d for 6 weeks. Profile of Mood States questionnaires were completed at baseline and following the intervention. No effect on overall mood was observed in the half a kiwifruit/d group; however, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
51
0
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(64 citation statements)
references
References 50 publications
3
51
0
10
Order By: Relevance
“…Most of the current evidence is correlational, but experimental and micro‐longitudinal research suggests a causal link between FV and well‐being. Two recent intervention studies showed that daily fruit consumption reduced self‐reported anxiety across a 10‐day period (Smith & Rogers, ), and that eating two kiwifruits per day resulted in significant improvements among emotionally vulnerable men in self‐reported ‘vigour,' which included reports of feeling cheerful, energetic, lively, and full of pep (Carr et al ., ). Similar experimental effects have been found for high doses of vitamins B and C, which are found abundantly in FV (Kennedy et al ., ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Most of the current evidence is correlational, but experimental and micro‐longitudinal research suggests a causal link between FV and well‐being. Two recent intervention studies showed that daily fruit consumption reduced self‐reported anxiety across a 10‐day period (Smith & Rogers, ), and that eating two kiwifruits per day resulted in significant improvements among emotionally vulnerable men in self‐reported ‘vigour,' which included reports of feeling cheerful, energetic, lively, and full of pep (Carr et al ., ). Similar experimental effects have been found for high doses of vitamins B and C, which are found abundantly in FV (Kennedy et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…The psychological benefits of FV are less established, but there is evidence that a higher intake is related to psychological well-being (Rooney et al, 2013). People who consume more FV show a lower incidence of depression (Adams & Colner, 2008;Allg€ ower, Wardle, & Steptoe, 2001;Carr, Bozonet, Pullar, & Vissers, 2013;Jacka et al, 2010;Kulkarni, Swinburn, & Utter, 2015;McMartin, Jacka, & Colman, 2013), greater happiness (Blanchflower, Oswald, & Stewart-Brown, 2012), and higher life satisfaction (Blanchflower et al, 2012;Grant, Wardle, & Steptoe, 2009;Lengyel, Tate, & Obirek-Blatz, 2009). For example, in a large sample of over 80,000 British people, a dose-response relationship was found between daily servings of FV and both life satisfaction and happiness.…”
mentioning
confidence: 99%
“…Por otro lado, la deficiencia de vitamina C se asocia con síntomas de depresión, fatiga e irritabilidad (35), y la suplementación con polivitamínicos ha demostrado mejorar el funcionamiento mental y el estado de ánimo de individuos diagnosticados de estrés (36), y también en los aparentemente sanos (37). Esto sugiere que las alteraciones del ánimo se pueden deber a deficiencias nutricionales, incluso subclínicas (38).…”
Section: Beneficios Para El Estado De áNimounclassified
“…Recientemente, el kiwi ha sido objeto de estudio como alimento con potencial efecto positivo en el estado de ánimo en individuos que tengan un consumo insuficiente de frutas y verduras y que tengan insuficiencia de vitamina C (< 50 mmol/L en plasma) (38). Estos resultados sugieren que dos kiwis proporcionan la cantidad óptima de vitamina C (unos 200 mg) (38).…”
Section: Beneficios Para El Estado De áNimounclassified
See 1 more Smart Citation